Situational Leadership in Special Education During COVID-19: A Study of SLB Negeri 2 Yogyakarta, Indonesia - Pratiwi, Dian (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This research aimed to explore the application of situational leadership by the Headmaster of SLB Negeri 2 Yogyakarta, Indonesia, in managing teaching and learning activities during the COVID-19 pandemic. Design/methods/approach – The study employed a qualitative descriptive methodology. Data was collected through interviews, observations, and document analysis from a selected group of school staff. Findings – The study revealed that the school's primary response consisted of curriculum adaptation, strategic use of technology, financial refocusing, and maintaining the mental wellness of the school community. Challenges such as remote communication difficulties, decreased physical and psychological health, sudden policy changes and reduced character education were identified. Strategies were utilized to tackle these issues, such as improved communication, enhanced character education, parental involvement, and using appropriate learning media. Research implications/limitations – The study underscores the significant role of situational leadership in managing crises in the educational sector. Further research is needed to substantiate these findings and delve deeper into the role of situational leadership during crises. Practical implications – The findings provide an understanding of how schools can adapt during crises, pointing towards strategic leadership as a crucial factor in maintaining the continuity of education. Schools facing similar challenges can take cues from the strategies employed by SLB Negeri 2 Yogyakarta. Originality/value – This study contributes uniquely by providing an in-depth exploration of the use of situational leadership in an educational setting during a global health crisis. It showcases the value of strategic leadership in ensuring effective teaching and learning despite unprecedented challenges.